A Development of Management Model for Community Participation in Education of The School Under Jurisdiction of The Office of The Basic Education Commission / การพัฒนารูปแบบการบริหารการมีส่วนร่วมของชุมชนในการจัดการศึกษาของสถานศึกษา สังกัดสำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน - สมคิด หาแก้ว, Somkid Hakaew / (Journal of Community Development Research (Humanities and Social Sciences), 2015)
การวิจัยครั้งนี้มีความมุ่งหมายเพื่อพัฒนารูปแบบการบริหารการมีส่วนร่วมของชุมชนในการจัดการศึกษาของสถานศึกษา สังกัดสำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน โดยมีจุดมุ่งหมายเฉพาะ 1) เพื่อศึกษาสภาพปัจจุบัน ปัญหาและปัจจัยสนับสนุน การบริหารการมีส่วนร่วมของชุมชนในการจัดการศึกษา 2) เพื่อสร้างและตรวจสอบคุณภาพของรูปแบบการบริหารการมีส่วนร่วมของชุมชนในการจัดการศึกษา และ 3) เพื่อประเมินยืนยันรูปแบบการบริหารการมีส่วนร่วมของชุมชนในการจัดการศึกษา การวิจัยครั้งนี้ มีวิธีดำเนินการ 3 ขั้นตอน คือ ขั้นตอนที่ 1 ศึกษาสภาพปัจจุบัน ปัญหาและปัจจัยสนับสนุนการบริหารการมีส่วนร่วมของชุมชนในการ จัดการศึกษา โดยศึกษาข้อมูลจากสถานศึกษาต้นแบบจำนวน 3 แห่ง ผู้ให้ข้อมูล ได้แก่ ผู้บริหารสถานศึกษา ข้าราชการครู และคณะกรรมการสถานศึกษาขั้นพื้นฐาน จำนวน 30 คน ขั้นตอนที่ 2 สร้างและตรวจสอบคุณภาพของรูปแบบการบริหารการมีส่วนร่วมของชุมชนในการจัดการศึกษา ผู้ให้ข้อมูล ได้แก่ ผู้เชี่ยวชาญ จำนวน 17 คน ประเมิน (ร่าง) รูปแบบการบริหารการมีส่วนร่วมของชุมชนในการจัดการศึกษาของสถานศึกษา และตรวจสอบคุณภาพรูปแบบด้วยวิธีการประชุมสัมมนาอิงผู้เชี่ยวชาญ (Connoisseurship) จำนวน 11 คน ขั้นตอนที่ 3 ประเมินยืนยันรูปแบบการบริหารการมีส่วนร่วมของชุมชนในการจัดการศึกษา ในด้านความเป็นไปได้และความเป็นประโยชน์ ผู้ให้ข้อมูล ได้แก่ ผู้บริหารสถานศึกษา และข้าราชการครูโรงเรียนๆ ละ 5 คน รวม 325 คน จำนวน 65 เขตพื้นที่การศึกษา สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าเฉลี่ยเลขคณิต ค่าร้อยละ ส่วนเบี่ยงเบนมาตรฐาน และวิเคราะห์เชิงเนื้อหา (Content Analysis)      ผลการวิจัย พบว่า สภาพปัจจุบัน ปัญหาและปัจจัยสนับสนุนการบริหารการมีส่วนร่วมของชุมชนในการจัดการศึกษาของสถานศึกษาต้นแบบ ในภาพรวมการมีส่วนร่วมของชุมชนในการจัดการศึกษา อยู่ในระดับมาก ปัญหาการมีส่วนร่วมของชุมชนในการจัดการศึกษา อยู่ในระดับน้อยที่สุด และปัจจัยสนับสนุนการบริหารการมีส่วนร่วมของชุมชนในการจัดการศึกษามีความสำคัญอยู่ในระดับมากที่สุด รูปแบบการบริหารการมีส่วนร่วมของชุมชนในการจัดการศึกษา ประกอบด้วย 4 องค์ประกอบ ได้แก่ 1) แนวคิดการบริหารการมีส่วนร่วมของชุมชนในการจัดการศึกษา 2) หลักการของรูปแบบการบริหารการมีส่วนร่วมของชุมชนในการจัดการศึกษา 3) วัตถุประสงค์ของรูปแบบการบริหารการมีส่วนร่วมของชุมชนในการจัดการศึกษา และ 4) วิธีดำเนินการ (PDCA) การบริหารการมีส่วนร่วมของชุมชนในการจัดการศึกษา ใน 4 ด้าน คือ การบริหารงานวิชาการ งานงบประมาณ งานบุคลากรและงานบริหารทั่วไป รูปแบบการบริหารการมีส่วนร่วมของชุมชน ในการจัดการศึกษา ในด้านความเป็นไปได้และความเป็นประโยชน์ ภาพรวมอยู่ในระดับมากที่สุด   คำสำคัญ : รูปแบบการบริหารโรงเรียน  การพัฒนารูปแบบ  การมีส่วนร่วมของชุมชน  การจัดการศึกษา  การประเมินรูปแบบ         The general objective of this research was to develop the administration model for community participation in education institutions under the office of basic education committee with the specific objectives as follows: 1) to study the current condition, problems and factors supporting the administration for community participation in education, 2) to construct and test the administration model and 3) to evaluate and ratify the administration model for community participation by using the research and development process which was divided into 3 stages as follows: Stage 1 was to study the condition. problems and factors supporting the administration for the community participation in educational institutions under the office of basic education by studying documents and 30 informants from three original educational institutions, Stage 2 was to construct and test the administration model from 17 experts and test the administration model and test the quality of the administration model by referring 11 experts in the seminar, Stage 3 was to evaluate and ratify the administration model for community participation from 325 administrators and teachers who are in charge of 4 tasks from 65 educational zones by opinion inquiries. The data were analyzed by mean, standard deviation, percentage and content analysis. The results from the study of current condition, problems and factors supporting the administration for the community participation in educational institutions from the 3 original educational institutions overall the community participation in education was in a high level. When considering by each item, it was found that the general administration of the community participation in education management of the educational institutions was ranked the first with a highest level. In terms of community participation problems it was in the least level. When considering by each item, budget administration was ranked the least: whereas, the supporting factors in community participatory administration were ranked with the highest levels. When considering by each item, the factors on power decentralization and good governance were ranked the first with the highest levels. 2) Administration model for community participation in education management of educational institutions under the office of basic education committee comprised 4 components as follows: component 1: concepts of community participation administration in education management. Component 2: Principles in community participation in educational management. Component 3: Objectives of administration model for community participation in educational management. Component 4: Procedures in community participation administration and success indicators. The result from overall components in community participation administration found that the model constructed by 17 experts, they all agreed with the overall mode. With 82.35 % and in the referring expert seminar, their opinions on accuracy, appropriateness and utilization were in highest levels and component 2 was ranked first. 3) The result of evaluation and ratification on administration model for community participation in educational institutions under the office of basic education committee was possible and beneficial in a highest level and when considering by each item it was found that the possibility and benefit were in the highest levels.   Keywords:   School Administration Model, The Model Development, Community Participation, Education Management, Evaluation Model
Keywords: รูปแบบการบริหารโรงเรียน การพัฒนารูปแบบ การมีส่วนร่วมของชุมชน การจัดการศึกษา การประเมินรูปแบบ School Administration Model, The Model Development, Community Participation, Education Management, Evaluation Model